Safety and efficacy of electrical stimulation for lower-extremity muscle weakness in intensive care unit 2019 Novel Coronavirus patients: A phase I double-blinded randomized controlled trial - Zulbaran-Rojas, Alejandro; Mishra, Ramkinker; Rodriguez, Naima; Bara, Rasha O.; Lee, Myeounggon; Bagheri, Amir Behzad; Herlihy, James P.; Siddique, Muhammad; Najafi, Bijan (Frontiers in Medicine, 2022)
Background Intensive care unit (ICU) prolonged immobilization may lead to lower-extremity muscle deconditioning among critically ill patients, particularly more accentuated in those with 2019 Novel Coronavirus (COVID-19) infection. Electrical stimulation (E-Stim) is known to improve musculoskeletal outcomes. This phase I double-blinded randomized controlled trial examined the safety and efficacy of lower-extremity E-Stim to prevent muscle deconditioning. Methods Critically ill COVID-19 patients admitted to the ICU were randomly assigned to control (CG) or intervention (IG) groups. Both groups received daily E-Stim (1 h) for up to 14 days on both gastrocnemius muscles (GNMs). The device was functional in the IG and non-functional in the CG. Primary outcomes included ankle strength (Ankles) measured by an ankle-dynamometer, and GNM endurance (GNMe) in response to E-Stim assessed with surface electromyography (sEMG). Outcomes were measured at baseline, 3 and 9 days. Results Thirty-two (IG = 16, CG = 16) lower extremities in 16 patients were independently assessed. The mean time between ICU admission and E-Stim therapy delivery was 1.8 ± 1.9 days (p = 0.29). At 3 days, the IG showed an improvement compared to the CG with medium effect sizes for Ankles (p = 0.06, Cohen’s d = 0.77) and GNMe (p = 0.06, d = 0.69). At 9 days, the IG GNMe was significantly higher than the CG (p = 0.04, d = 0.97) with a 6.3% improvement from baseline (p = 0.029). E-Stim did not alter vital signs (i.e., heart/respiratory rate, blood saturation of oxygen), showed no adverse events (i.e., pain, skin damage, discomfort), nor interfere with ICU standard of care procedures (i.e., mechanical ventilation, prone rotation). Conclusion This study supports the safety and efficacy of early E-Stim therapy to potentially prevent deterioration of lower-extremity muscle conditions in critically ill COVID-19 patients recently admitted to the ICU. If confirmed in a larger sample, E-Stim may be used as a practical adjunctive therapy. Clinical trial registration [https://clinicaltrials.gov/], identifier [NCT04685213].